The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1469-8749.2012.04391.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy tube feeding of children with cerebral palsy: variation across six European countries

Abstract: ABBREVIATION GTF Gastrostomy tube feedingAIM To compare the prevalence of gastrostomy tube feeding (GTF) of children with cerebral palsy (CP) in six European countries.METHOD Data on 1295 children (754 males, 541 females; mean age 5y 11mo, range 11y 2mo, min 6mo, max 11y 8mo) with CP born from 1999 to 2001 were collected from geographically defined areas in six European countries; four of the areas covered the whole country. Distribution of CP was unilateral 37%, bilateral 51%, dyskinetic 8%, and ataxic 4%. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 23 publications
6
57
0
1
Order By: Relevance
“…7 The use of tube-feeding was consistent with studies made in Norway and Denmark 3 and in the south of Sweden. 5 However, the observed prevalence in the present study was about twice as high as that found in previous studies regarding difficulties with chewing and swallowing, 9 drooling, 9 and deviant lip position.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…7 The use of tube-feeding was consistent with studies made in Norway and Denmark 3 and in the south of Sweden. 5 However, the observed prevalence in the present study was about twice as high as that found in previous studies regarding difficulties with chewing and swallowing, 9 drooling, 9 and deviant lip position.…”
Section: Discussionsupporting
confidence: 58%
“…1 Impaired eating is associated with poor growth 2,3 and problems with chewing and swallowing may jeopardize respiration. 4,5 Notably, the most common causes of death in young individuals with CP are secondary respiratory diseases.…”
mentioning
confidence: 99%
“…İhsan Doğramacı Çocuk Hastanesi Gastroenteroloji Polikliniğinde çalışan hekimlerin tümünden uzman görüşü alınarak yeniden düzen-lenip son hâli oluşturulmuştur. [1][2][3][4][5][6][7][8][9][10][11] Anket soruları, ebeveynlerin bakımla ilgili davranışlarını değer-lendirmeye yönelik soruları içermektedir. Bu form, gastrostomi ile beslenen çocukların ve ebeveynlerinin tanıtıcı özelliklerine, çocuğun hastalığa iliş-kin bilgilerine, ebeveynlerin beslenme, ilaç uygulama davranışları ve pansuman uygulama davranışlarına yönelik bilgilere ulaşılmasını sağlayan toplam 32 sorudan oluşmaktadır.…”
Section: Gastrostomi Tüpü Ile Beslenen çOcuklarınunclassified
“…Research across six European countries, for example, has demonstrated considerable variation in the use of GFT and the age at which they are placed, which could be attributed, in part, to variations in clinical practice. 15 Delaying surgery may add to the stress already experienced by caregivers. Ongoing assessment of parental psychosocial support needs and their ability to cope with oral/nasogastric tube feeding, with a view to moving toward feeding by a GFT, should form an essential aspect of clinical care.…”
Section: Introductionmentioning
confidence: 99%